Dos fenomenólogas piensan la República: María Zambrano y Edith Stein - Eduardo González Di Pierro (Revista de Filosofía Open Insight, 2010)
Both Edith Stein and María Zambrano thought and wrote about politics from the same perspective: phenomenology. They agree on republicanism as the best way of government. This paper aims to track the elaboration of their political thought, first separately, then comparing and distinguishing it, towards the construction of a phenomenology of the Republic.